Amazon Riparian People’s Exposure to Legacy Organochlorine Pesticides and Methylmercury from Catfish (Ageneiosus brevifilis) Intake - Guida, Yago de Souza; Lino, Adan Santos; Nepomuceno, Raquel Capella Gaspar; Meire, Rodrigo Ornellas; Torres, João Paulo Machado; Malm, Olaf (Orbital: The Electronic Journal of Chemistry, 2018)
The worldwide massive use of organochlorine pesticides (OCPs) and mercury (Hg) is taken as an environmental threat due to their high toxicity, potential for long-range transport, bioaccumulation and persistence. Both, OCPs and Hg, were widely used in the Brazilian Amazon region and deserve more attention in terms of environmental and public health. Focusing on expanding the knowledge about impacted areas and its consequences for local people, this study measured concentrations of OCPs and Hg in catfish (Ageneiosus brevifilis) samples. Moreover, a non-target analysis of organohalogen contaminants was carried out by means of full-scan screening. DDT and methylmercury showed the highest concentration values, ranging from 101 to 2061 µg kg-1 w.w. and 629 to 2009 µg kg-1 w.w., respectively. Pentachloroanisole was the only non-target organohalogenated compound identified and it was present in all samples. Estimated daily intake values did not exceed the safe reference limits proposed by the World Health Organization for OCPs, with the exception in some cases of heptachlor. On the other hand, the safe reference value of methylmercury was surpassed in all the fish samples. Results dismiss a recent input of OCPs due to greater contribution of pesticide metabolites, however, they point out a health risk hazard to riparian people. The concentrations of methylmercury and total dichlorodiphenyltrichloroethane, were up to one order of importance higher than other contaminants, which endorses that this region is still a hotspot for these contaminants. DOI: http://dx.doi.org/10.17807/orbital.v10i4.1071